2014
DOI: 10.1093/nar/gku736
|View full text |Cite
|
Sign up to set email alerts
|

Genomic HEXploring allows landscaping of novel potential splicing regulatory elements

Abstract: Effective splice site selection is critically controlled by flanking splicing regulatory elements (SREs) that can enhance or repress splice site use. Although several computational algorithms currently identify a multitude of potential SRE motifs, their predictive power with respect to mutation effects is limited. Following a RESCUE-type approach, we defined a hexamer-based ‘HEXplorer score’ as average Z-score of all six hexamers overlapping with a given nucleotide in an arbitrary genomic sequence. Plotted alo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
81
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 78 publications
(85 citation statements)
references
References 57 publications
3
81
1
Order By: Relevance
“…Upregulation of D2b use following G I2 -1 inactivation indicated that an SR protein binding site could be located within exon 2b. We had previously found an enhancing element located downstream of D2 in a HEXplorer-based screen of total HIV-1 mRNA (13). Continuing analysis of this element here showed that the enhancer ESE2b strongly activates D2b and simultaneously inhibits D2, which is facilitated by binding of SRSF10 and Tra2.…”
Section: Discussionsupporting
confidence: 61%
See 4 more Smart Citations
“…Upregulation of D2b use following G I2 -1 inactivation indicated that an SR protein binding site could be located within exon 2b. We had previously found an enhancing element located downstream of D2 in a HEXplorer-based screen of total HIV-1 mRNA (13). Continuing analysis of this element here showed that the enhancer ESE2b strongly activates D2b and simultaneously inhibits D2, which is facilitated by binding of SRSF10 and Tra2.…”
Section: Discussionsupporting
confidence: 61%
“…We used the sequence CCAAACAA (23) as a splicing-neutral reference and the very strongly enhancing purine-rich SRE HIV-1 GAR E42 fragment as a positive control (GAR contains GAA or GAG repeats [R is A or G]) (20,22). As expected, fragment IV, covering G I2 -1, did not support downstream splice donor use, while ESE2b (ESE 5005-5032 [13]), contained in fragment III, enhanced D2b use. Neither fragment I nor fragment II led to increased eGFP expression (Fig.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations